Thiophilicity is a determinant of bioaccumulation in benthic fauna. (1st February 2022) - O'Callaghan, Irene; Fitzpatrick, Dara; Sullivan, Timothy
Abstract: Aquatic contamination can settle into sediments, where it complexes with organic matter and becomes bioavailable. The resulting bioaccumulation of these contaminants by benthic fauna poses a serious threat due to the potential for trophic transfer. This paper offers an insight into the heterogenous accumulation behavior of different elements, and the consequences for ecological risk. In this study, we present field quantification of sediment-associated bioaccumulation factors (BAFS ) in freshwater benthic macroinvertebrates. 17 elements were quantified using ICP-MS in sediment and Asellus aquaticus and Gammarus sp. samples. Previously published reports of contaminant concentrations in freshwater and marine sediments and benthic fauna were likewise analyzed to provide a complementary picture of bioaccumulation across contaminants and taxa. We demonstrate that the BAFS correlates strongly with the thiophilicity of the elemental contaminants, as defined by (Kepp, 2016), for all strata examined. These findings support the hypothesis that thiol-mediated processes, such as that of metallothionein, play a larger role in bioaccumulation than typically afforded. In conclusion, we demonstrate the potential for the thiophilic scale to act as a predictor of accumulation potential. Graphical abstract: Image 1 Highlights: Accumulation correlates strongly with thiophilicity across orders and environments. Results support a thiol-based bioaccumulation process. Bioavailability of contaminants can be predicted using the thiophilic scale.